LA DEUDA HISTÓRICA DEL BICENTENARIO: EL DERECHO INDÍGENA PERUANO VISTO DESDE EL SUR: THE HISTORICAL DEBT OF THE BICENTENARY: PERUVIAN INDIGENOUS LAW SEEN FROM THE SOUTH - Espezúa Salmón, Boris (2021)
At the beginning of the 20th century in southern Peru, particularly in Puno and Cusco, a concern for Peruvian indigenous law arose. Now, with regard to the 200 years of the Republic, it is worth remembering what motivations the promoters of said proposal had, what activities they developed, what type of resonance their contributions had in the national spectrum. The present work is framedw ithin the historical debts that the country has had, the issues that it has left aside, that it has neglected, or deliberately has not paid due attention to. One of them is the original, indigenous, ancestral Law that is now approached as intercultural justice, or legal pluralism, and that has just begun to be treated as a new theory and trend that should deserve a place in the construction of a new country in the next years.next years.